Employment and knowledge: Prospects for HE graduates’ employability in knowledge-intensive services - Valente, Ana Claúdia (Conferência - Investigação e Intervenção em Recursos Humanos, 2016)
The tertiarization of the Portuguese economy is already very evident in the sectorial composition of employment. In 2013, the service sectors represented in Portugal 65% of total employment. Although the service sectors have also been affected by the economic crisis, its resilience to the negative effects of the crisis on labour market was much higher than other sectors. From the wide range of services, knowledge-intensive services (KIS) were those that registered the highest increase in employment between 2008 and 2013. The study presented here discusses the role that knowledge-intensive services, in particular knowledge-intensive market services (excluding the financial services) and high-tech knowledge-intensive services, can have in promoting youth employment in Portugal. The increasing outsourcing, on a global scale, of complex and highly qualified activities has stimulated the rapid growth of these sectors. The competition for talent, although intense and global, is opening up new job opportunities for young higher education graduates. The study uses statistical data to analyse the recent evolution of employment in these two sectors, its variation by levels of education and age groups, and their contribution to total employment. Based on the CEDEFOP projections for Portugal, we discuss the potential employment opportunities estimated in KIS up to 2025. This analysis is complemented with qualitative data on changing job and skills’ requirements in these sectors, collected through literature reviewing and a set of interviews with the industry and employers’ associations. Main research findings indicate a significant potential for job creation in KIS over the next decade and a growing demand for qualifications. Medium-level qualifications will tend to prevail and about a 1/3 of the jobs will require higher education. However, the digital revolution is changing the way services are designed and delivered to customers, requiring new service models. Business services are becoming more technology-dependent or, at least, more technology-enabled. Also the intangible nature of KIS requires a strong co-production with costumers and open modes of innovation which are increasingly demanding a broad set of soft and hard-technical skills. Preparing young graduates with the right mix of skills seems essential to take advantage of the number of jobs the KIS tend to create, especially when youth unemployment is high. This study seeks to contribute to the debate on how higher education can improve the employability of its graduates by exploring statistic data on recent employment trends and early identifying labour market dynamics on a sectorial basis.